Gülcin Wilhelm: Generation Koffer. Die zurückgelassenen Kinder. Berlin: Orlanda Frauenverlag 2011. 174 sider. ISBN 978-3-936937-83-1. Pris: 18 euro. - Mørck, Yvonne (Tidsskriftet Antropologi, 2012)
Intet resumé